2012
DOI: 10.1038/aps.2012.22
|View full text |Cite
|
Sign up to set email alerts
|

18β-Glycyrrhetinic acid preferentially blocks late Na current generated by ΔKPQ Nav1.5 channels

Abstract: Aim:To compare the effects of two stereoisomeric forms of glycyrrhetinic acid on different components of Na + current, HERG and Kv1.5 channel currents. Methods: Wild-type (WT) and long QT syndrome type 3 (LQT-3) mutant ∆KPQ Nav1.5 channels, as well as HERG and Kv1.5 channels were expressed in Xenopus oocytes. In addition, isolated human atrial myocytes were used. Two-microelectrode voltage-clamp technique was used to record the voltage-activated currents. Results: Superfusion of 18β-glycyrrhetinic acid (18β-GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Taking this into consideration, the drugs currently available in clinics are not satisfactory. Previous studies have revealed that GA can block peak and late I Na [19, 20]. In our task group, the results suggested that GA not only blocks I Kr (HERG) and I Ks but also inhibits I Ca-L .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Taking this into consideration, the drugs currently available in clinics are not satisfactory. Previous studies have revealed that GA can block peak and late I Na [19, 20]. In our task group, the results suggested that GA not only blocks I Kr (HERG) and I Ks but also inhibits I Ca-L .…”
Section: Discussionsupporting
confidence: 66%
“…These findings might help to elucidate the traditional use of licorice in therapy for cardiovascular disorders [19]. It has also been reported that 18 β -GA has significant potential for development as a novel antiarrhythmic agent and for treating myocardial ischemia by preferentially blocking the I Na,L [20]. However, the effects of GA on the potassium channel, especially the rapid and slow components of the delayed rectifier potassium current, are not clearly defined.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study demonstrated that GA reduced peak I Na and late I Na in Xenopus oocytes [20]. It has also been reported that GA exerts antiarrhythmic effects in the setting of myocardial ischemia via the blockage of Ina and Ica-L [21]. Additionally, GA inhibited potassium currents in both ventricular myocytes and HEK293 cells [22].…”
Section: Introductionmentioning
confidence: 77%
“…Furthermore, barbaloin also significantly inhibited ATX II-induced I Na.L enhancement. These findings indicated that barbaloin eliminates ATX II-induced EADs by inhibiting I Na.L enhancement; hence, these currents may be a promising target for the treatment of arrhythmias [29] .…”
Section: Discussionmentioning
confidence: 99%